Institutional sheltering and deinstitutionalization: an integrative review in psychology (Emancipação, 2020)
This study presents an integrative literature review about deinstitucionalization of sheltered children and adolescents. To achieve this goal, we have mapped papers in the CAPES Portal, SciELO or Lilacs and published between 2003 and 2019 within the area of psychology. There were found 24 articles in accordance with the established criteria. The main topics covered in the articles were: family, adoption and deinstitutionalization after reaching full legal age. It was found that there was an expansion of the studies about the shelter and deinstitutionalization processes and that it is seen in ambiguous ways, sometimes being treated as a protective alternative, sometimes referred to as harmful to the sheltered person. It was possible to notice there is a lack of studies about deinstitutionalization after reaching full legal age. This is a serious gap, since a great amount of adolescent leave the institutions through this way.
Keywords: Sheltering; Deinstitutionalization; Children and adolescents